SEKOLAH PEMUDA: MENDORONG PERAN GENERASI MUDA DALAM INOVASI DAN KEWIRAUSAHAAN UNTUK EKONOMI DAERAH - Ridhoh, M. Yunasri; Nasir, Sri Astuti; Iswardhani, Indri; Sarah, Nulthazam; Sandira, Nur Fadilah Ayu (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The community service program entitled Youth School: Encouraging the Role of Young Generation in Innovation and Entrepreneurship for Regional Economy was carried out to promote the contribution of youth in strengthening local economic development based on regional potential. This activity aimed to shape youth with strong character, innovation capability, and social vision, particularly in the context of entrepreneurship development. The program was conducted using a participatory-educative approach, emphasizing active involvement of participants in learning sessions, discussions, and critical reflection. It involved youth and university students across Makassar. The results of the program indicated an increased understanding among participants regarding local entrepreneurship issues, digital literacy, and demographic bonus opportunities. Furthermore, participants were able to formulate applicable and contextual action plans, such as establishing digital-based youth business communities, marketing local products, and initiating basic management training. This program proves that with proper educational support and facilitation, youth can become key actors in advancing innovation-based local economic development.